Productivity and Income Analysis of Red Onion Farming on Marginal Land in Kaswari Village South Kaledupa Sub-district, Wakatobi Regency - Yana Lestari; Bahari, Bahari; abdi, abdi (International journal of technology and education research, 2025)
This research aims to (1) Find out the productivity of shallot farming on marginal land in Kaswari Village, South Kaledupa District, Wakatobi Regency (2) Find out the income of shallot farming on marginal land in Kaswari Village, South Kaledupa District, Wakatobi Regency. This research was carried out in January-May 2024. The sampling method was simple random sampling, with a total of 35 farmers. Based on the research results, it shows that (1) Analysis of the productivity and income of shallot farming on marginal land is usually lower than on fertile land due to various factors. Marginal land is land that has limitations for agricultural activities which affect farming productivity. The productivity of shallots obtained was 3,714 Kg/ha. (2) The total cost of shallot farming in Kaswari Village per season is IDR 955,865, where the total income from shallot farming activities is IDR 14,523,000, the income of shallot farmers in Kaswari Village is IDR 13,567,135.